Die Rolle finanzieller Faktoren im US-amerikanischen Wirtschaftsboom der 90er Jahre - Evans, Trevor (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
Although the most recent US economic expansion began in 1991, rapid growth and job creation only date from 1996. This faster growth was driven principally be consumer demand, but while the stock market bubble that developed from 1996 might explain spending by upperincome groups, most share holdings are small. A more significant financial factor behind the boom has been the rapid growth of borrowing by both companies and households, whose debts now stand at a record high. This borrowing has been financed by massive inflows of financial capital from abroad, and the possibility that these could turn around is the greatest threat facing the US economy as the expansion comes to an end.